Improving skills and care standards in the support workforce for older people: a realist synthesis of workforce development interventions. Issue 8 (26th August 2016) - Williams, L; Rycroft-Malone, J; Burton, C R; Edwards, S; Fisher, D; Hall, B; McCormack, B; Nutley, S M; Seddon, D; Williams, R
Abstract : Objectives: This evidence review was conducted to understand how and why workforce development interventions can improve the skills and care standards of support workers in older people's services. Design: Following recognised realist synthesis principles, the review was completed by (1) development of an initial programme theory; (2) retrieval, review and synthesis of evidence relating to interventions designed to develop the support workforce; (3) 'testing out' the synthesis findings to refine the programme theories, and establish their practical relevance/potential for implementation through stakeholder interviews; and (4) forming actionable recommendations. Participants: Stakeholders who represented services, commissioners and older people were involved in workshops in an advisory capacity, and 10 participants were interviewed during the theory refinement process. Results: Eight context–mechanism–outcome (CMO) configurations were identified which cumulatively comprise a new programme theory about 'what works' to support workforce development in older people's services. The CMOs indicate that the design and delivery of workforce development includes how to make it real to the work of those delivering support to older people; the individual support worker's personal starting points and expectations of the role; how to tap into support workers' motivations; the use of incentivisation; joining things up around workforce development; getting the right mix of people engaged in the design and delivery of workforce development programmes/interventions; taking a planned approach to workforce development, and the ways in which components of interventions reinforce one another, increasing the potential for impacts to embed and spread across organisations. Conclusions: It is important to take a tailored approach to the design and delivery of workforce development that is mindful of the needs of older people, support workers, health and social care services and the employing organisations within which workforce development operates. Workforce development interventions need to balance the technical, professional and emotional aspects of care. Trial registration number: CRD42013006283.